Expression of Tau Protein and Tau mRNA in gastric carcinoma - Li, Chun-hui; Pan, Li-Hui; Sahi, Rajina; Xing, Zhao; Yu, Cheng; De-Li, Zhang (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: To provide theoretical basis for the gastric carcinoma pathogenesis and the clinical targeted therapy. Materials and Methods: We detected the expression of Tau protein and Tau mRNA in 60 cases of gastric carcinoma tissues (observation group) and 10 cases of normal gastric tissues (control group). Immunohistochemisty was adopted to detect the expression of Tau protein in normal and carcinomatous gastric tissue. Tau mRNA was detected by RT-PCR in normal and carcinomatous gastric tissue. To analyse the experimental data combined clinical pathology with statistics. Results: The expression of Tau protein in carcinomatous gastric tissue was higher than that in normal gastric tissue (P<0.05). The expression of Tau protein and Tau mRNA in well differentiated and moderately differentiated was lower than that in poorly differentiated gastric carcinoma (P<0.05). The expression of Tau protein and Tau mRNA in gastric carcinoma without lymph node metastasis was lower than that in gastric carcinoma with lymph node metastasis (P<0.05). The expression of Tau mRNA in carcinomatous gastric tissue was higher than that in normal gastric tissue (P<0.05). Conclusion: Tau protein and Tau mRNA were significant differences between normal gastric tissue and gastric carcinoma, also were concerned with differentiation in grade and lymph node metastasis of gastric carcinoma. Asian Journal of Medical Sciences Vol.7(1) 2015 20-23